Komentar Bung Jebret - Anwar Anwar; Ernik Hasnawati (Universitas Muslim Maros, 2019)
The high level of people’s enthusiasm in watching football competitition, as one of the most popular sports, has stimulated the growth and the development of broadcast innovations in various media. Football guides or commentators put themselves as the spirit giver of the match. One of the most popular football commentators in the Indonesian football reportage is Valentino Simanjuntak, popularly known as Bung Jebret, who has been in the spotlight in recent years. His way of comment on his reportage has become a new language phenomenon in semantic point of view, and this article explores this. This study was conducted through the Youtube and Blog media that recorded and re-aired the football match which was commented on by Valentino Simanjuntak in between February and November 2017. Data was collected using referring method, by listening to 40 Valentino Simanjuntak’s expression obtained from Youtube accounts and Blog links. The results shows that all expressions of the language of reportage Valentino Simanjuntak uses unique diction. In the semantics point of view, his expressions are classifies into four types of meanings, namely denotation (expressions is in accordance with the original meaning), connotation meanings (expressions and meanings are interrelated), figurative meanings (expressions and meanings are not corresponded) and associated meaning (parable). The selection of arbitrary diction makes it difficult for listeners (viewers) to understand, thus one cannot get the meaning without deeply comprehend what is behind the expression. This has become a new lighter in responding to linguistic phenomena that are increasingly prevalent along with the development of media and technology.